Management of Post-cardiotomy Shock - Eric J Hall; Alexander I Papolos; P Elliott Miller; Christopher F Barnett; Benjamin B Kenigsberg (US Cardiology Review)
Patients undergoing cardiac surgery experience significant physiologic derangements that place them at risk for multiple shock phenotypes. Any combination of cardiogenic, obstructive, hemorrhagic, or vasoplegic shock occurs commonly in post-cardiotomy patients. The approach to the diagnosis and management of these shock states has many facets that are distinct compared to non-surgical cardiac intensive care unit patients. Additionally, the approach to and associated outcomes of cardiac arrest in the post-cardiotomy population are uniquely characterized by emergent bedside resternotomy if the circulation is not immediately restored. This review focuses on the unique aspects of the diagnosis and management of post-cardiotomy shock.